Environmental contamination and risk factors for transmission of highly pathogenic avian influenza A(H5N1) to humans, Cambodia, 2006-2010. Issue 1 (December 2016) - Ly, Sowath; Vong, Sirenda; Cavailler, Philippe; Mumford, Elizabeth; Mey, Channa; Rith, Sareth; Van Kerkhove, Maria; Sorn, San; Sok, Touch; Tarantola, Arnaud; Buchy, Philippe
Abstract Background Highly pathogenic avian influenza A (H5N1) virus has been of public health concern since 2003. Probable risk factors for A(H5N1) transmission to human have been demonstrated in several studies or epidemiological reports. However, transmission patterns may differ according to demographic characteristics of the population and local practices. This article aggregates these data from three studies with data collected in the previous surveys in 2006 and 2007 to further examine the risks factors associated with presence of anti-A(H5) antibodies among villagers residing within outbreak areas. Methods We aggregated 5-year data (2006–2010) from serology survey and matched case-control studies in Cambodia to further examine the risks factors associated with A(H5N1) infection among villagers in the outbreak areas. Results Serotesting among villagers detected 35 (1.5 % [0–2.6]) positive cases suggesting recent exposure to A(H5N1) virus. Practices associated with A(H5N1) infection among all ages were: having poultry cage or nesting area under or adjacent to the house (OR: 6.7 [1.6–28.3];p  = 0.010) and transporting poultry to market (OR: 17.6 [1.6–193.7];p  = 0.019). Practices found as risk factors for the infection among age under 20 years were swimming/bathing in ponds also accessed by domestic poultry (OR: 4.6 [1.1–19.1];p  = 0.038). Association with consuming wild birds reached borderline significance (p  = 0.066). Conclusion Our results suggest that swimming/bathing in contaminated pond water and close contact with poultry may present a risk of A(H5N1) transmission to human.